Serum 1,3-βD-Glucan assay in the diagnosis of invasive fungal disease in neonates - Mackay, Cheryl Anne (PAGEPress Publications, 2011)
Invasive fungal disease is a significant cause of morbidity and mortality in the neonate. The current study aims to assess the 1, 3-βD-Glucan (BG) assay in a prospective analysis in neonates with suspected fungaemia. A multicentre, prospective cohort study was conducted in Johannesburg, South Africa. The study included 72 neonates with clinically suspected late onset sepsis who were at high risk of fungaemia. A BG assay was performed on each patient and correlated with a sepsis classification based on the full blood count, C-reactive protein and blood culture results as no fungaemia, possible fungaemia, probable fungaemia or definite fungaemia. Sensitivity and specificity of the BG assay at levels of 60 pg/mL are 73.2% and 71.0% respectively and at levels of 80 pg/mL are 70.7% and 77.4% respectively. Positive and negative predictive values at 60 pg/mL are 76.9% and 66.7% respectively and at 80 pg/mL are 80.6% and 66.7% respectively. The area under the receiver operating curve is 0.753. The BG assay is a useful adjunct to the diagnosis of invasive fungal disease in neonates. It does, however, need to be considered in the context of the clinical picture and supplementary laboratory investigations.